Design of Solar Panel Utilization as a Mobile Phone Charger Station Box in Online Ojek Places - Falacchi, Muhammad Azhar; Ayusta Lukita Wardani; Widiyartono, Mahendra; Rahmadian, Reza (Proceeding of International Joint Conference on UNESA, 2024)
One of the problems in the field of electrical energy is the limited source of coal energy which is the main source of energy from steam power plants in Indonesia. To reduce electricity dependence on this limited coal, a renewable energy source is needed. Solar panels are one of the producers of electrical energy sourced from sunlight that always shines and does not cause pollution. The use of solar panels is the best solution for current conditions as an alternative energy source to be utilized as a source of cellphone battery charging at online motorcycle taxi stations. This final project aims to design, manufacture and install a solar power plant as the main source on the handphone charger station box at the online motorcycle taxi place. The SOLAR POWER installation consists of 1 100 WP solar panel, 1 10A SCC, 1 12V 65Ah battery, 1 600W inverter, AC and DC MCBs, cables, power outlets, Arduino uno, relays, LCD, RFID, solenoid door lock.